Electron-deficient boron-based catalysts for C-H bond functionalisation - Ma, Yuanhong; Lou, Shao-Jie; Hou, Zhaomin (Chemical Society reviews, 2021)
In contrast to transition metal-catalysed C-H functionalisation, highly efficient construction of C-C and C-X (X = N, O, S, B, Si, etc. ) bonds through metal-free catalytic C-H functionalisation remains one of the most challenging tasks for synthetic chemists. In recent years, electron-deficient boron-based catalyst systems have exhibited great potential for C-H bond transformations. Such emerging systems may greatly enrich the chemistry of C-H functionalisation and main-group element catalysis, and will also provide enormous opportunities in synthetic chemistry, materials chemistry, and chemical biology. This article aims to give a timely comprehensive overview to recognise the current status of electron-deficient boron-based catalysis in C-H functionalisation and stimulate the development of more efficient catalytic systems. This review article provides a comprehensive overview to recognise the current status of electron-deficient boron-based catalysis in C-H functionalisations.